An analysis of the development of Shanghai's tourism industry - Hui, Wang; Tang, John C.S.; Sununta Siengthai; Dimmitt, Nicholas J.; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
As we known, Shanghai, as a metropolis and the largest economic center in China, is now making an effort to develop its tourism industry. Tourism has become one of the city's economic pillars. This research study described the current situation of Shanghai's tourism industry, with focusing on analyzing international and domestic tourism. In the past year, international and domestic tourists and a total tourism income were increased every year. The year 2005 is booming year of Shanghai's tourism industry, generating valued-added 58.43 billion Yuan and the ratio of valued added of tourism industry to GDP is 6.4%. The results of the study indicate that Shanghai's tourism industry have done well so far, it still will encounter opportunities in the future, such as, World Exhibition 2010, Disneyland, and Beijing 2008 Olympics. However, Shanghai's tourism development may also meet the following serious challenges: RMB appreciation, bad relationships between China-Japan, and tightening competition. Based on the results, provide the recommendations to policy makers to ensure that the overall matching services are optimized in structure, getting on the track of virtuous cycle and doubling their benefits, thus making the international tourism industry of Shanghai develop rapidly and healthy
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M. BA.) - Asian Institute of Technology, 2006
Keywords: Tourism -- China -- Shanghai